Orexinergic system in the locus coeruleus modulates the CO2 ventilatory response - Vicente, Mariane C. [UNESP] (2016)
The orexins are hypothalamic neuropeptides involved in an array of functions such as regulation of sleep/wake states and chemoreception to CO2/pH. The locus coeruleus (LC) is a chemosensitive site and expresses an extensive population of orexin receptor 1 (OX1R). We tested the hypothesis that OX1Rs located in the LC participate in the ventilatory response to hypercapnia in a vigilance state and diurnal cycle-dependent manner. For this, we performed unilateral injections of SB-334867 (OX1R antagonist, 5 mM) into the LC of male Wistar rats and evaluated the ventilatory response to 7 % CO2 during wakefulness and sleep in the dark and light phases of the diurnal cycle. Hypercapnia induced an increase in ventilation (VE) in all groups compared to normocapnic values. However, during the dark phase, but not in the light phase, SB-334867 injection promoted an attenuation of the hypercapnic chemoreflex during wakefulness (VE: vehicle, 1502.6 ± 100 mL kg−1 min−1 vs SB-334867, 1200.3 ± 70.0 mL kg−1 min−1) but not during sleep (VE: vehicle, 1383.0 ± 113.9 vs SB-334687, 1287.6 ± 92.1 mL kg−1 min−1), due to changes in tidal volume (VT). We suggest that projections of orexin-containing neurons to the LC contribute, via OX1Rs, to the hypercapnic chemoreflex during wakefulness in the dark phase.